Very fast transient overvoltage calculation and evaluation for 500‐kV gas insulated substation power substation with double circuit and long gas insulated substation busbar - Runyu Fu; Jianguo Wang; Jianping Wang; Mi Zhou; Cai Li; Yating Zhao; Yadong Fan (IET Generation, Transmission & Distribution, 2023)
Abstract The operation of disconnectors in gas insulated substation (GIS) or power plant will produce very fast transient overvoltage (VFTO), which is considered to have serious harm to transformer longitudinal insulation and other high‐voltage equipment insulation. VFTO may also lead to secondary circuit failure. In this paper, the holistic modelling of 500 kV GIS step‐up substation equipment with a double circuit and long GIS busbar in a coastal power plant is established using Electromagnetic Transient Program (EMTP). The authors calculated the VFTO waveform that may be generated in different operations of the GIS substation. The authors analyze the amplitude and frequency characteristics of the VFTO waveform at lightning arresters and the entrance of transformers and find that the amplitude of VFTO at the entrance of #1 MT is less than its impulse withstand voltage. In some cases, the VFTO waveform at the entrance of #1 MT has high‐frequency content with fast attenuation. The VFTO waveform generated when operating the disconnector close to the arrester will cause the arrester to act many times and count frequently in a short time.